KECERDASAN BUDAYA DALAM PROSES BANTUAN PENYELESAIAN MASALAH - Agung Nugraha (Journal of Innovative Counseling : Theory, Practice, and Research, 2018)
This article aims to analyze cultural intelligence in the problem-solving process with a focus on the study of the role of cultural intelligence for counselors and counselors in counseling services. Intensive literature review of the role of cultural intelligence in counseling services is a research methodology of this paper. Therefore, this paper is expected to contribute to the development of science in the field of problem-solving assistance services, especially cross-cultural counseling services. This paper is expected to be one of the treasures of multicultural competence development in the implementation of problem solving assistance services.